Mujeres extranjeras en las cárceles españolas - Ribas Mateos, Natalia; Martínez, Alexandra (Sociedad y Economía, 2003)
This paper shows that the tendencies toward economic globalization go parallel to the tightening of control policies affecting the flux of foreign populations in an epoch of half-closed borders and strong penalization of drug trafficking. It explores the way in which an international division of labor is forged by means of global migrations, and describes how this process is traversed by routes of drug traffic and networks of sexual exploitation. The results presented here are the product of a research project advanced in Spanish penal institutions: as a paradox, these institutions become strategic spaces for research on account of their strange combination of openness and closure, of personal mobility and seclusion.